Broo someone help pllss
![Broo someone help pllss class=](https://us-static.z-dn.net/files/d60/ec26ad161e3790ba22878278f68ccb73.png)
========================================================
Explanation:
15 - 2.5x is the same as 15 + (-2.5)x
Then we can swap the terms to get -2.5x+15
Therefore, the original equation is the same as -2.5x+15 = 40
To solve this equation, we follow PEMDAS in reverse. So instead of starting with the "P", we start with the "S". There's no subtraction operations to undo, so we move onto the "A". There is an additional operation to undo, which is the +15
To undo the +15, we subtract 15 from both sides
-2.5x+15 = 40
-2.5x+15-15 = 40-15
-2.5x = 25
The next step after this would be to divide both sides by -2.5 to undo the multiplication. The -2.5x means "-2.5 times x".